(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Despite its strategic importance, the literature has failed to clearly define practical flexibility. Empirical studies have led to varied and often contradictory results based on various conceptualizations and measurement techniques. In the field of human resource management this paper proposes a structure to define and measure functional flexibility. Researchers tried to explain the word by categorizing past meanings and adding an integrative design to the process. Scholars discuss and justify the need for a certain degree of practical flexibility in human resource management procedures in the first part of this essay to support the ability of organizations to respond to a changing environment. From this perspective this capability is seen as a relevant source of competitive advantage. Scholars propose a new framework for functional flexibility and a measurement model based on our theoretical analysis that could help generate further studies on this topic. This structure should be used as a starting point for creating a realistic flexibility rating scale. In the last part of the article potential lines of research to be gained from this assessment are discussed. Scholars focus on the need to study how human resource discovery and exploitation can be flexibly incorporated into human resource management approaches.